The Influence of Experiential Marketing on Tourism Visitor Satisfaction In Tanjung Sakti (Sindang Panjang Agrotourism and Warm Water) - Elvera Elvera; Sastra Mico (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to determine whether there is an influence of Experiential Marketing on Visitor Satisfaction and to find out how much the Experiential Marketing Variable has on Visitor Satisfaction in Tanjung Sakti Tourism in Sindang Panjang and Air Warm Agrotourism. This study uses an associative research method with a quantitative approach. There are two variables used in this study, namely Experiential Marketing (X) and Visitor Satisfaction (Y). This data collection was obtained by distributing questionnaires to Tanjung Sakti Tourism Visitors at Sindang Panjang and Air Warm Agrotourism. The sample used in this study was 100 respondents using Simple Linear Statistical Analysis and Sampling techniques. The results of the Simple Linear Regression Analysis Test in this study indicate that Experiential Marketing has a positive effect on visitor satisfaction. It can be seen from the Simple Regression Analysis, namely: Y = 0.798 + 0.475. Which is a constant value of 0.798, the regression coefficient value of Experiential Marketing has a positive effect, which means that if the Experiential Marketing Strategy increases by one unit, visitor satisfaction will increase by 0.475 units. The Experiential Marketing Strategy has a significant effect on Visitor Satisfaction which can be seen from the results of the t-test where the significant value is 0.000, which means it is smaller than 0.05 so the hypothesis is accepted.